Pengaruh Penambahan Carboxymethyl Cellulose (CMC) Terhadap Sifat Mekanik Dan Biodegradasi Plastik Biodegradable Berbasis Selulosa Bakteri –Polietilen Glikol (PEG) Dari Air Kelapa (Cocos nucifera) - Juniyas Aditia; Ananda Putra (Departemen Kimia FMIPA UNP, 2023)
Biodegradable plastics are plastics that are easily degraded by microorganisms. This study aims to determine the effect of adding carboxymethyl cellulose additives to biodegradable plastics based on PEG bacterial cellulose from coconut water (cocos nucifera) and to determine physical, mechanical, and biodegradable properties. This study used 14% polyethylene glycol 400 as a plasticizer with variations in the mass of carboxymethyl cellulose, namely 2 gr, 4 gr, 6 gr, and 8 gr. The results of testing the physical properties obtained are the value of % water content and the degree of swelling increase with the addition of the mass of carboxymethyl cellulose. The maximum result from testing the mechanical properties obtained was in the addition of carboxymethyl cellulose 6 gr with a tensile strength value of 101.05 MPa, elasticity of 2544.83 MPa, and elongation of 13.78 %. In the biodegradation test carried out by burial for 15 days, the results obtained that more carboxymethyl cellulose added the ability of plastic biodegradation increased. The characteristics of the functional group using FTIR showed that there was no new functional group formed, and the results of the characteristics of the degree of crystallinity in biodegradable plastics obtained the degree of pure SB plastic kristanility was 83.75%, SBPEG was 70.68%, and SBPEG-C 6 gr was 74.20%.